Genetic Basis of Carnivorous Leaf Development - Agrawal, Arpita; Pareek, Ashwani; Dkhar, Jeremy (Frontiers in Plant Science, 2022)
Plant carnivory is often manifested as dramatic changes in the structure and morphology of the leaf. These changes appear to begin early in leaf development. For example, the development of the Sarracenia purpurea leaf primordium is associated with the formation of an adaxial ridge, whose growth along with that of the leaf margin resulted in a hollow structure that later developed into a pitcher. In Nepenthes khasiana, pitcher formation occurs during the initial stages of leaf development, although this has not been shown at the primordial stage. The formation of the Utricularia gibba trap resulted from the growth of the dome-shaped primordium in both the longitudinal and transverse directions. Recent research has begun to unfold the genetic basis of the development of the carnivorous leaf. We review these findings and discuss them in relation to the flat-shaped leaves of the model plant Arabidopsis.